A single-chip digitally calibrated 5.15-5.825-GHz 0.18-μm CMOS transceiver for 802.11a wireless LAN. - Vassiliou, I. (IEEE Journal of solid state circuits)
The drive for cost reduction has led to the use of CMOS technology in the implementation of highly integrated radios. This paper presents a single-chip 5-GHz fully integrated direct conversion transceiver for IEEE 802.11a WLAN systems, manufactured in 0.18-μm CMOS. The IC features an innovative system architecture which takes advantage of the computing resources of the digital companion chip in order to eliminate I/Q mismatch and achieve accurately matched baseband filters. The integrated voltage-controlled oscillator and synthesizer achieve an integrated phase noise of less than 0.8° rms. The receiver has an overall noise figure of 5.2 dB and achieves sensitivity of -75 dBm at 54-Mb/s operation, both referred to the IC input. The transmit error vector magnitude is -33 dB at -5-dBm output power from the integrated power-amplifier driver amplifier. The transceiver occupies an area of 18.5 mm2.